Research on the amino acid composition in semi-smoked sausages containing lentils, juniper and thyme - Маркович, Ірина Іллівна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with the possibilities of using vegetable raw materials in the meat processing industry. The study presents recipes of smoked sausages, specifies the amino acid composition, analyzes the amino acid score, and reveals the indicators of the biological value of proteins in new types of semi-smoked sausages that contain the flour of lentil sprouts and non-germinated lentils as well as spicy and aromatic plants with the aim of putting them into production. Semi-smoked sausages show an increase in the amount of essential amino acids by 2.146 mg/100g (sample 1) and by 1.217 mg/100 g (sample 1.1) in comparison with the reference sample. An increase in the amount of essential amino acids is observed in all the samples: 2.216 mg/ 100 g (sample 2), 0.728 mg/ 100 g (sample 2.1), 2.766 mg/100 g (sample 3), and 1.722 mg/100 g (sample 3.1) in comparison with the reference sample. Semi-smoked sausages also demonstrate a significant increase in the use of the limited amino acid valine: by 2.81 % in sample 1, by 5.63 % in sample 1.1, sample 2, and sample 3.1, and by 4.22 % in sample 3. The amino acid score of the majority of amino acids in semi-smoked sausages is optimal. All products also contain a significant amount of lysine. In semi-smoked sausages with the use of non-germinated lentil flour, the amino acid score of methionine + cystine grows from 1.73 % to 7.82 % in comparison with the reference sample. In semi-smoked sausages with the use of lentil sprouts flour, the amino acid score of fenilalanin + tyrosine grows from 7.29 % to 10.94 % in comparison with the reference sample. Amino acids contained in semi-smoked sausages are readily absorbed by the body: the KRAS of samples 1.1-3.1 is 14.38 %, 16.72 %, and 8.63 % lower than that of samples 1-3. The biological value of such sausages is also higher than of the reference sample—by 0.5 % in sample 1.1 and by 1.2 % in sample 2.1. The highest rate of comparable redundancy was found in the reference sample, which is 1.78 %. In semi-smoked sausages with lentil sprouts flour, it is by 4.73 % and 9.46 % lower in comparison with sample 1; it is by 5.05 %, 9.5 %, and 14.04 % lower in the research samples than in the reference sample. In semi-smoked sausages with non-germinated lentil flour, this indicator is also lower than in the reference sample—by 10.6% (sample 2.1.). It has been found that the substitution of raw meat with lentil sprouts flour in an amount of 1.5 to 2.0 kilos per 100 kilos of raw meat is expedient and it raises the energy value of the new types of semi-smoked sausages.